ARP2/3 localization in Arabidopsis leaf pavement cells: a diversity of intracellular pools and cytoskeletal interactions - Zhang, Chunhua; Mallery, Eileen L.; Szymanski, Dan (Frontiers in Plant Science, 2013)
In plant cells the actin cytoskeleton adopts many configurations, but is best understood as an unstable, interconnected track that rearranges to define the patterns of long distance transport of organelles during growth. Actin filaments do not form spontaneously; instead filament nucleators, such as the evolutionarily conserved actin-related protein (ARP) 2/3 complex, can efficiently generate new actin filament networks when in a fully activated state. A growing number of genetic experiments have shown that ARP2/3 is necessary for morphogenesis in processes that range from tip growth during root nodule formation to the diffuse polarized growth of leaf trichomes and pavement cells. Although progress has been rapid in the identification of proteins that function in series to positively regulate ARP2/3, less has been learned about the actual function of ARP2/3 in cells. In this paper, we analyze the localization of ARP2/3 in Arabidopsis leaf pavement cells. We detect a pool of ARP2/3 in the nucleus, and also find that ARP2/3 is efficiently and specifically clustered on multiple organelle surfaces and associates with both the actin filament and microtubule cytoskeletons. Our mutant analyses and ARP2/3 and actin double labeling experiments indicate that the clustering of ARP2/3 on organelle surfaces and an association with actin bundles does not necessarily reflect an active pool of ARP2/3, and instead most of the complex appears to exist as a latent organelle-associated pool.